Case Report: Acute Spinal Cord Myelopathy in Patients With COVID-19 - Khedr, Eman M.; Karim, Ahmed A.; Soliman, Radwa K. (Frontiers in Neurology, 2020)
COVID-19 is typically associated with fever and severe respiratory symptoms including dry cough and dyspnea. However, COVID-19 may also affect both central and peripheral nervous systems. To date, the incidence rate of spinal cord involvement in COVID-19 is not known and the pathogenesis is still not fully understood. We report here two female patients admitted to Assiut University Hospitals/Egypt during the period from first of July to August 10, 2020. Both presented with a positive SARS-CoV-2 polymerase chain reaction (PCR) nasopharyngeal swab, elevated serum d-dimer and ferritin levels, and bilateral ground glass appearance in a CT chest scan. The first was a 60-year-old female with acute onset of flaccid paraplegia 10 days after flu-like symptoms, in whom MRI revealed transverse myelitis. The second was a 21-year-old female with symptoms of acute quadriplegia, fever, headache, and anosmia in whom an MRI scan revealed long cervico-thoracic myelopathy. Anterior spinal artery occlusion and possibly transverse myelitis were considered as differential diagnosis of long segment myelopathy.